Friendly urban environments from the perspective of children and older people - Dayse da Silva Albuquerque; Isolda de Araújo Günther (Estudos de Psicologia (Campinas))
Abstract Objective This study aimed to identify how children and older people evaluate their residential environments, considering their individual capacities and the pressures of the physical urban environment. Method Using an exploratory, descriptive and qualitative approach, interviews with photographs were conducted with children and older people in two locations. The interviews followed a semi-structured script and photographs were presented according to the environmental characteristics of each location. Results The analyses revealed a pursuit of independence and autonomy in the use of spaces, to varying degrees, according to each group’s abilities to cope with environmental pressure situations. The findings indicate that the relationship with the urban environment is shaped by daily experiences, memories, and the environmental resources available to these individuals in their residential environments. Conclusion Facilitators and barriers intersperse in daily life, demanding alternative use of spaces and modifications of scenarios in order to turn them friendlier for urban populations.